Cultural Themes Related to Oral Health Practices, Beliefs, and Experiences in Nigeria: A Scoping Review - Taofeek Kolawole Aliyu; Olusegun Stephen Titus; Oluwabunmi Tope Bernard; Omolola Titilayo Alade; Adebola Oluyemisi Ehizele; Moréniké Oluwátóyìn Foláyan (Oral)
The objective of this scoping review was to map out the cultural themes related to oral health practices, beliefs, and experiences in Nigeria; explore mythologies about oral health in Nigeria; identify the perceived cultural significance of oral health within the Nigerian communities; and determine the implications of study findings for oral health promotion and intervention strategies. This was a scoping review. A systematic literature search was conducted in PubMed, Cochrane Library, Web of Science, Google Scholar, and CINAHL. Published studies in peer-reviewed journals written in English that investigated culture and oral health were included. All forms of literature reviews, editorials, or opinion pieces were excluded. Information on the study characteristics and population characteristics, cultural determinants of oral health, oral health outcomes, and the methods used to assess cultural factors and oral health outcomes was extracted. A narrative synthesis of the findings was conducted to identify key themes in the literature. The 37 articles, published between 1998 and 2024, that met the eligibility criteria wrote on the prevalence of a culture of self-medication and self-care, myths that affect utilization of oral health services, cultures that expose people to increased risk of poor oral health, and cultural norms, beliefs, and practices that facilitate oral health. The findings emphasize the need for culturally tailored strategies to improve oral health literacy and reduce disparities. This review underscores the potential to foster community engagement, trust, and sustainable improvements in oral health outcomes by aligning oral health promotion efforts with Nigeria’s culture. In conclusion, cultural norms, beliefs, and practices can be barriers and facilitate oral health in Nigeria. Identifying and understanding the norms, beliefs, and practices that affect oral health can help improve oral health education and promotion so that they are culturally relevant and effective.